Determination of Parents’ Resilience with Autistic child in Baghdad City - Ismael, Bayda’a A.; Jacoub, Shirroq M. (Journal of the Faculty of Medicine Baghdad, 2013)
Background:Many parents of autistic child do well despite their child’s disability, they have the ability to withstand hardship and rebound from adversity, and becoming more strengthened, parents have managed to overcome the constant challenge by using their resilience to adapt well in the face of adversity. Patients and Methods: A Descriptive analytical study was carried out from May 25, 2009 to June 20, 2010 in order to determine parents’ resilience in dealing with the impact of raising a child with autism. A purposive (non-probability) sample of (100) parents raising a child with autism who was attending the out patient psychiatric clinic at Child’s Central Teaching Hospital in Baghdad City. Data was collected by filling the questionnaire .The questionnaire form consist from two parts; the first part is concerned with the demographic characteristics of the child and demographic characteristics of the parents; the second part consists of six domains of resilience and contains 34 items that describe the parents’ resilience.Objectives: The study aimed to assesses the level of parents’ resilience with autistic childandtofind out the relationship between parents’ resilience and some child characteristics such as child gender, child age, child age at diagnosis, type and place of treatment; also to the parents characteristics such as parents’ gender, age, mother age at child birth, educational level, marital status, occupation, income, number of children in the family, and number of autistic children in the family. Results: Results of the study indicate that parents of autistic child experience moderate level of resilience level of resilience; also there were significant differences between parents’ resilience and types and place of treatment, mothers’ age at child’s birth,level of education, and income. Conclusions: The study concludes that parents have to face burden to provide necessary care for their child; despite the many difficulties associated with autism; they can maintain a solid familial life style.